Designed for Learning: use of Skill Tracker in Veterinary education - Phil Lionel Ramsey; Sajid Khan; Jenny Weston; Neil Marshall (APMBA (Asia Pacific Management and Business Application), 2016)
Although learning is a natural process, many of the systems designed to support education do not contribute positively to the experience of students. This paper reports on the design of Skill Tracker, a software system developed at Massey University to manage processes around student skill acquisition, and initially applied to the university’s Veterinary Science program. The software has been designed around guiding ideas relevant to learning in a professional context: the “progress principle” and Communities of Practice. The paper outlines how these ideas have shaped the design of the software. While Skill Tracker enables the university to collect data that informs the management of the Veterinary School, the underlying purpose of the system is to enhance the experience of students. In order to do achieve this goal it is necessary to understand a key dilemma in any educational innovation: the need to integrate technology and pedagogy.